PEDAGOGICAL SKILL: THE MAIN CRITERION OF THE EDUCATIONAL PROCESS (Spectrum Journal of Innovation, Reforms and Development, 2024)
Pedagogical skill plays a decisive role in the success of the educational process. Teachers with effective pedagogical skills have the ability to create an interesting and meaningful learning experience, help students develop, and facilitate optimal learning outcomes. This scientific article covers the importance of pedagogical skills as the main criterion of the educational process. It explores the basic components of pedagogical skill, illuminates their importance, and provides insight into its application in stimulating student learning and achievement. Understanding and developing pedagogical skills is essential for teachers to meet the diverse needs of students and create an impressive educational experience.